2007
DOI: 10.1038/sj.cgt.7701081
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of Flt3 ligand and GM-CSF genes modulates immune responses induced by HER2/neu DNA vaccine

Abstract: DNA vaccine and dendritic cells (DCs)-based vaccine have emerged as promising strategies for cancer immunotherapy. Fms-like tyrosine kinase 3-ligand (Flt3L) and granulocyte-macrophage-colony-stimulating factor (GM-CSF) have been exploited for the expansion of DC. It was reported previously that combination of plasmid encoding GM-CSF with HER2/neu DNA vaccine induced predominantly CD4þ T-cell-mediated antitumor immune response. In this study, we investigated the modulation of immune responses by murine Flt3L an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…The third reason may be that VP1 antigen could be better processed in antigen-presenting cells (APCs) when DNA plasmids are administered separately. Herein, our observation was not in agreement with previous studies showing that intramuscular injection of bicistronic plasmid provoked more potential systemic immune responses than the mixture of two monocistronic plasmids encoding antigen and adjuvant (Yo et al, 2007;Tang et al, 2008). However, there is also a lot of evidence indicating that simultaneous delivery of antigens and adjuvants in nanoparticles ensures that both agents can be efficiently expressed and delivered into the same APC or T cell population and the maximal adjuvant effects could be achieved (Singh et al, 2001;Vajdy et al, 2004).…”
Section: Optimization Of Adjuvant Ltn Administrationcontrasting
confidence: 99%
See 1 more Smart Citation
“…The third reason may be that VP1 antigen could be better processed in antigen-presenting cells (APCs) when DNA plasmids are administered separately. Herein, our observation was not in agreement with previous studies showing that intramuscular injection of bicistronic plasmid provoked more potential systemic immune responses than the mixture of two monocistronic plasmids encoding antigen and adjuvant (Yo et al, 2007;Tang et al, 2008). However, there is also a lot of evidence indicating that simultaneous delivery of antigens and adjuvants in nanoparticles ensures that both agents can be efficiently expressed and delivered into the same APC or T cell population and the maximal adjuvant effects could be achieved (Singh et al, 2001;Vajdy et al, 2004).…”
Section: Optimization Of Adjuvant Ltn Administrationcontrasting
confidence: 99%
“…Previous studies have suggested that the temporal and spatial coexpression of antigens and adjuvants seems to be critical for optimal immune priming. Yo et al (2007) found that compared with two monocistronic plasmids, coexpression of FMS (colony stimulating factor 1 receptor)-like tyrosine kinase 3 receptor ligand and granulocyte-macrophage colony-stimulating factor genes in a bicistronic plasmid could promote a potent CD8 + T cell immunity induced by human epidermal growth factor 2 (HER2)/neu DNA vaccine against bladder tumors. Fusion plasmid encoding human papillomavirus L1 protein with regulated upon activation normal T cell expressed and secreted (RANTES) generated higher frequency of specific splenic T cells than the combination of plasmids encoding L1 and RANTES separately (Kim et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of immune enhancement by FL appears to be due to its ability to increase the number of DC recruited to the immunization site to elicit robust antigen-specific cellular responses (45, 46). Moreover, another study demonstrated that co-expression of FL and GM-CSF considerably improved the ability of splenic DC to mature and present antigen to T cells, which was associated with an increase in the number of DC recruited to the immunization site, production of higher levels of IFN-γ and increased cytotoxicity of splenocytes in vaccinated mice (28). This study, which employed HER2/neu (a target antigen for anticancer therapy) as a DNA vaccine to study the adjuvant effect of murine Flt3L and GM-CSF in different forms of plasmid construction further demonstrated that FL targets DCs that constitutively express the receptor CD135.…”
Section: Discussionmentioning
confidence: 99%
“…It binds to the fms-like tyrosine kinase receptor Flt3/Flk2 (CD135) and in collaboration with other growth factors, stimulates the proliferation and differentiation of various blood cell progenitors. For example, it dramatically increases immune cell number and has been exploited for dendritic cell (DC) expansion (28). Intranasal administration of Flt3L with P6 protein of non-typeable Haemophilus influenzae (NTHi) to mice increased dendritic cell number in the nasal-associated lymphoid tissue, significantly elevated P6-specific nasal mucosal IgA and serum IgG titers and boosted nasopharyngeal NTHi clearance (29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation